Loan Monitoring Costs and Loan Payment in SACCOs: A Case Study of Mitooma People's SACCO in Mitooma Town Council Mitooma District. - Mugarura, Adison (Kabale University, 2024)
This study aimed to analyze the influence of loan monitoring costs and loan payment in SACCOs specifically Mitooma People's SACCO. It was supported by the following research objectives; to find out the Loan Monitoring techniques used by Mitooma people's SACCO- Mitooma town council, Minooka district; to find out the effects of loan monitoring on loan repayment and recovery in SACCOs within Mitooma district, to identify the challenges faced by loan officers in monitoring loans in SACCOs. The study used a descriptive and cross-sectional survey research design was used and it described phenomena as they existed. The sample size comprised 80 respondents. The study findings revealed that physical verification of the borrower's workplace, physical verification of the borrower's mortgaged property or hypothecated, presentation of collateral security to the SACCO, giving early notifications to the borrower, pledging for the collaterals is another feature of the interest rate in most semi-formal financial institutions and internal auditing were some of loan monitoring techniques used by Mitooma People's SACCO. The study findings also revealed that loan clearance and dealing with the defaulters affects the recipients negatively, loan monitoring also determines whether the remaining contingency reserves for cost and schedules are adequate, loans with high loan monitoring have higher monthly payments or take longer to pay off than loans with low loan monitoring, therefore the higher loan monitoring charged by most financial institutions as a loaning requirement hinders loan request which affects the socio-economic status of the recipients and women are given little or no loans because they lack collaterals as a requirement from the financial institution and this retards development, the interest rate mostly does not favor women who are considered to be the agents for development. Women's access to formal sources of loans is restricted because they often lack collateral as a requirement needed by the microfinance and the inability to retrieve all loans due to the relocation of business activity or the residence of defaulters also affects loan monitoring in SACCOs affects of loan monitoring on loan repayment and recovery in SACCOs. From the study findings on challenges faced by loan officers in monitoring loans in SACCOs, respondents revealed that poor transport infrastructure to the rural places, clients who provide wrong information to the bank, multiple borrowing by the clients in different borrowing institutions, social factors showing a weak influence on loan default, lack of liquidity monitoring system, inadequate managerial competencies and political interference and huge microfinance losses are caused by outright loan default were some of the challenges faced by loan officers in monitoring loans in SACCOs.